Effect of Cinnamon (Cinnamomum burmannii) Bark Oil on Pancreatic Histopathology of white Rats (Rattus norvegicus) Induced with Streptozotocin - Budiastuti1 , Reni Utami2 , Mustofa Helmi Effendi3 , and Hani Plumeriastuti4 * (Indian Journal of Forensic Medicine & Toxicology, 2020)
The purpose of this research was to understand the effect of the cinnamomum (Cinnamomum burmannii)bark oil (CBO) on the pancreatic histopathology white rat (Rattus norvegicus) with diabetes mellitus. Thevariables taken were the diameter and the number of Langerhans Island in the pancreatic of white male ratswhich had been induced by streptozotocin (STZ). This research using diabetic rat induced by streptozotocinintraperitoneally with single dose of 45 mg/kg BW. Samples consist of fifty rats were divided into fivegroups, negative control group (K-) was not induced by streptozotocin, which treatment by giving CMCNa 1%, positive control group (K+) was induced by streptozotocin without CBO, group P1 was induced bystreptozotocin and gave CBO 100 mg/kgBW, group P2 was induced by streptozotocin and gave CBO 200mg/kgBW, group P3 was induced by streptozotocin and gave CBO 400 mg/kgBW daily for 14 days period.The results showed that cinnamomum bark oil (CBO) with dose 200 mg/kgBW (P2) was significantly higher(p<0,05) than group P1, group P3 and positive control group (K+). It can be concluded that CBO can be usedto improve pancreatic function of STZ induced in diabetic rats